Primary biliary cholangitis with features of autoimmune hepatitis in a 19-year-old adolescent with 14q24.1q24.2 deletion: a case report - Wang, Yi-Wei; Chao, Hsun-Chin; Wang, Huei-Shyong; Lin, Ju-Li; Chang, Chih-Chen; Huang, Shiu-Feng (Frontiers in Pediatrics, 2023)
Introduction Primary biliary cholangitis (PBC) is a rare and chronic autoimmune liver disease characterized by the progressive destruction of small intrahepatic bile ducts that may eventually lead to cirrhosis. PBC with features of autoimmune hepatitis (AIH) has rarely been reported in pediatric patients with genetic defects. We present the case of an adolescent with chromosome 14q24.1q24.2 deletion who was given the diagnosis of stage IV PBC with features of AIH.Case presentation A 19-year-old male adolescent with multiple congenital abnormalities and an intellectual disability presented with abnormal liver enzymes levels and pruritus for more than 5 years. Laboratory examinations revealed elevated levels of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, and gamma-glutamyl transpeptidase. After the exclusion of viral hepatitis, alpha-1 antitrypsin deficiency, Wilson's disease, and other genetic cholestatic liver diseases by laboratory tests and whole exome sequencing, a liver biopsy was performed and stage IV PBC was diagnosed. Notably, features of AIH were also noted in the histopathological report, indicating the presence of PBC with AIH features. The patient responded well to a combination therapy of ursodeoxycholic acid and steroids. Array comparative genomic hybridization analysis performed to study the congenital abnormalities revealed a 3.89 Mb 14q24.1q24.2 deletion.Conclusion PBC with AIH features has rarely been reported in an adolescent with a chromosomal abnormality. The present case can increase awareness for early-onset PBC and its possible correlation with chromosomal defects.